2009
DOI: 10.1093/nar/gkp1034
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of CHOP translation by phosphorylated eIF4E under stress conditions

Abstract: Cells respond to environmental stress by inducing translation of a subset of mRNAs important for survival or apoptosis. CHOP, a downstream transcriptional target of stress-induced ATF4, is also regulated translationally in a uORF-dependent manner under stress. Low concentration of anisomycin induces CHOP expression at both transcriptional and translational levels. To study specifically the translational aspect of CHOP expression, and further clarify the regulatory mechanisms underlying stress-induced translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 44 publications
(52 reference statements)
0
65
0
Order By: Relevance
“…One mechanism by which MNK alters cell fate is by altering the translation of specific mRNAs. To date, there have been numerous mRNAs identified as translationally regulated targets of MNK, including those encoding cytokines IL-17 (32) and pro-inflammatory TNF␣ (79), the anti-apoptotic protein Mcl-1 (28), ribosomal proteins S19 and L32 (19), proteins involved in cell proliferation (CDK2, CDK8, CDK9, HIF-1␣, KAP1, proliferating cell nuclear antigen, PIAS1, and RASSF1 (19)), proteins involved in cell cycle progression (cyclins A, B, D1, and D3 (19,78)), cancer-related proteins (HER2 (21), VEGF (35), and IRF-1 (84)), transcription factors (RFLAT-1 (46), CHOP (85), and ␤-catenin (25)), and neuronal proteins (Arc, ␣CaMKII, PKM-, calmodulin, BDNF (86), and PEM1 (20)). Translation of many of these mRNAs is also responsive to eIF4E levels, indicating a cap-and eIF4E-dependent mechanism of translation: HIF-1␣ (19), HER2 (21), Mcl-1 (28), cyclin D1 (87,78), VEGF (88), RFLAT-1 (46), ␤-catenin (25), and Arc (86).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which MNK alters cell fate is by altering the translation of specific mRNAs. To date, there have been numerous mRNAs identified as translationally regulated targets of MNK, including those encoding cytokines IL-17 (32) and pro-inflammatory TNF␣ (79), the anti-apoptotic protein Mcl-1 (28), ribosomal proteins S19 and L32 (19), proteins involved in cell proliferation (CDK2, CDK8, CDK9, HIF-1␣, KAP1, proliferating cell nuclear antigen, PIAS1, and RASSF1 (19)), proteins involved in cell cycle progression (cyclins A, B, D1, and D3 (19,78)), cancer-related proteins (HER2 (21), VEGF (35), and IRF-1 (84)), transcription factors (RFLAT-1 (46), CHOP (85), and ␤-catenin (25)), and neuronal proteins (Arc, ␣CaMKII, PKM-, calmodulin, BDNF (86), and PEM1 (20)). Translation of many of these mRNAs is also responsive to eIF4E levels, indicating a cap-and eIF4E-dependent mechanism of translation: HIF-1␣ (19), HER2 (21), Mcl-1 (28), cyclin D1 (87,78), VEGF (88), RFLAT-1 (46), ␤-catenin (25), and Arc (86).…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was reported that p-eIF4E binds more efficiently to capped mRNAs (17), suggesting that the affinity of phosphorylated eIF4E for 4E-BP1 is decreased. Moreover, Chen et al (19) reported that p-eIF4E binds less well to 4E-BP1 than the unphosphorylated form. In our coimmunoprecipitation and Western blot studies, p-eIF4E seemed to show a weaker affinity for 4E-BP1 than total eIF4E in MDA-MB 468 cells, but not in MDA-MB 231 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although eIF4E phosphorylation on Ser209 was discovered some time ago, it remains unclear whether phosphorylation increases or decreases eIF4E affinity for the cap-structure. Early data indicated that eIF4E phosphorylation increased the affinity for capped mRNAs, whereas other studies have shown that eIF4E phosphorylation actually decreases affinity for the cap-structure and capped oligoribonucleotides (15,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 98%
“…is a C/EBP homologous protein that plays crucial roles in cellular translational stress conditions, making epithelial cells sensitive to xenobiotic-induced injuries (33). In the present study, chemical ER stresses were assessed for their effects on stress-inducible CHOP expression and its association with inflammatory cytokine production.…”
Section: Chop Is Positively Involved In Er-activated Il-8 Production mentioning
confidence: 99%